Narrowing Yield Gaps and Enhancing Nitrogen Utilization for Summer Maize (Zea mays L) by Combining the Effects of Varying Nitrogen Fertilizer Input and Planting Density in DSSAT Simulations - Ren, Hao; Li, Zhenhai; Cheng, Yi; Zhang, Jibo; Liu, Peng; Li, Rongfa; Yang, Qinglong; Dong, Shuting; Zhang, Jiwang; Zhao, Bin (Frontiers in Plant Science, 2020)
As a result of increased attention being paid to sustainable agricultural development, improving crop yield and nitrogen use efficiency has become a widespread concern. In the study presented in this paper, the crop growth model implemented by the Decision Support System for Agrotechnology Transfer (DSSAT) software was used to simulate three management treatments during five maize growing seasons in the HHHP of China. The three treatments were the super-high-yield cultivation pattern (SH), the optimized nutrient and density management pattern (ONM), and the local farmer's practice cultivation pattern (FP). The model parameters were calibrated using data from actual physiological measurements taken between 2012 and 2014, and the simulated performance was validated using data from measurements taken between 2015 and 2016. Subsequently, the potential yield and yield gap for different yield levels were analyzed and the practices of fertilization and density optimization under the ambient experiment conditions were evaluated. Results show that: 1) With respect to the model performance figures, the root mean square error (RMSE), normalized root mean squared errors (NRMSE) and index of agreement (d) 1,171 (kg ha-1), 12% and 0.84 for the yield. These results show that the model is viable for this experiment. 2) The average potential yield of summer maize over five years was 15.58 t ha-1, but the yield achieved with the AFP treatment amounted to only 55% of the potential yield, suggesting a large potential for yield increases. 3) Through analyzing the response of the simulated yield to varying the planting density and nitrogen fertilizer application, we found that the optimal planting density for summer maize in HHHP is 9 plants m-2, and the optimal nitrogen fertilizer application amount is 246 kg ha-1. The results also suggest that the maximum yield actually achieved by optimizing nitrogen application and planting density is less than 73% of the potential yield, which implies that other measures, such as irrigation, sowing dates and pest control, need to be considered in order to further narrow the observed yield gaps.